Supervisor Feedback - Hayman, Marilyn J. (Canadian Journal of Counselling and Psychotherapy, 2012)
This study investigated the effectiveness of supervisor feedback in contributing to learning three basic counselling skills. It was hypothesized that trainees given supervisor feedback would learn the skills more effectively than trainees given no supervisor feedback or no training at all, regardless of previous counsellor training. Sixty-four counsellor trainees were randomly assigned to 12 groups (supervisor feedback, no supervisor feedback, and no treatment control) for three training sessions. Raters then judged the counselling skills ef- fectiveness on a post-test interview using a Likert-type scale. Results indicated that con- trary to the prediction, counselling skills were learned most effectively by those students who had no feedback from the supervisor, but evaluated themselves and heard feedback from peers.